Fear of the coronavirus and the stock markets - Štefan Lyócsa; Eduard Baumöhl; Tomáš Výrost; Peter Molnár (ZBW – Leibniz Information Centre for Economics, 2020)
Since the outbreak of the COVID-19 pandemic, stock markets around the world have experienced unprecedented declines, which have resulted in extremely high stock market uncertainty, measured as price variation. In this paper, we show that during such periods, Google Trends data represent a timely and valuable data source for forecasting price variation. Fear of the coronavirus, as measured by Google searches is predictive of future stock market uncertainty for stock markets around the world. Google searches were also strongly correlated with the evolution of physical contagion (the number of new cases), and with implemented nonpharmaceutical interventions. The effect of pandemic-related policies on investors' attention and fear is thus very well captured by Google Trends data.
Keywords: G01; G15; 330; Coronavirus; Stock market; Uncertainty; Panic; Google Trends